The natural genius of ants - Culley, Betty (Crown Books for Young Readers, 2022)
Harvard, his younger brother, and his dad move to Maine for the summer, where they start an ant farm with their neighbor Neveah and learn about ants, each other, and how to forgive yourself when things do not go as planned.